2009
DOI: 10.1586/egh.09.36
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open left lateral hepatectomy

Abstract: Laparoscopic liver surgery is becoming more popular, and many high-volume liver centers are now gaining expertise in this area. Laparoscopic left lateral hepatectomy (LLLH) is a standardized and anatomically well-defined resection and may transform into a primarily laparoscopic procedure for cancer surgery or living donor hepatectomy for transplantation. Five case-control series were identified comparing a total of 167 cases (86 cases of LLLH plus 81 cases of open left lateral hepatectomy). Groups were matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The development of this technique has been limited during this time due to difficulty reproducing basic open liver surgery maneuvers, risks of bleeding and pulmonary embolism, and fear of compromising oncologic resection by tumoral cell seeding [20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…The development of this technique has been limited during this time due to difficulty reproducing basic open liver surgery maneuvers, risks of bleeding and pulmonary embolism, and fear of compromising oncologic resection by tumoral cell seeding [20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Benefits of LLS include less intraoperative blood loss, less postoperative complications, decreased need for analgesics, faster functional recovery, shorter postoperative stay, and a cosmetic benefit. [1][2][3][4][5][6][7][8][9] In addition, some studies have demonstrated the cost-effectiveness of LLS, [10][11][12] thus resulting in benefits for both individual patients and healthcare institutions. These promising results have promptly increased the interest in LLS worldwide 1,2 and the first randomized controlled trials of laparoscopic vs. open liver surgery have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conclusions only represent a small group of patients. Moreover, the oncologic risks of laparoscopic liver resection for HCC are still under investigation, especially the surgery resection margin, the potential for tumor cell seeding through trocar‐site or peritoneal dissemination and tumor recurrence 13 . This study aims to use meta‐analysis of comparative studies to dig deeper on the aspect of surgical and oncologic outcomes of patients with HCC undergoing laparoscopic versus open hepatectomy.…”
Section: Introductionmentioning
confidence: 99%